Is DAA Treatment Associated with HBV Reactivation? Results from ERCHIVES. (4th October 2017) - Butt, Adeel; Yan, Peng; Shaikh, Obaid; Abou-Samra, Abdul-Badi
Abstract: Background: Reactivation of HBV infection has been reported in patients with HCV treated with newer directly acting antiviral agents (DAAs). Magnitude of this problem and its consequences are not fully understood. Methods: Using ERCHIVES, a well-established national database of HCV infected Veterans, we identified all persons who received DAA treatment for >28 days. We determined the proportion of patients who had HBV viral reactivation (≥1 log10 increase in HBV DNA from baseline), seroconversion (from HBsAg or HBeAg seronegative to seropositive), or flare of hepatitis (HBV viral reactivation plus ALT increase ≥10 times baseline value) at anytime after initiating DAA treatment. We also determined factors associated with HBVr using Cox regression analysis. Results: We identified 43, 137 persons on DAA therapy. Among those with available follow-up data, overall HBV reactivation was observed in 795 persons. HBV viral reactivation was observed in 4.8% (17/352), clinical hepatitis in 0.3% (1/350), seroconversion in 16.0% (695/4339) and ALT flare in 0.2% (85/41652). In a Cox proportional hazards model, factors associated with increased risk of HBV reactivation were black race, male sex, alcohol use or dependence, and detectable HBV DNA at baseline (table). Treatment with any regimen was associated with a significantly lower risk (number of persons on sofosbuvir/daclatasvir and elbasvir/grazoprevir were small to make meaningful inferences) of HBV reactivation. Conclusion: Among HCV infected persons treated with a DAA regimen, HBV viral reactivation and HBV seroconversion are common, but clinical hepatitis or ALT flares are rare. DAA regimens are not associated with HBV reactivation. Disclosures: A. Butt, Merck: Investigator, Grant recipient